Diagnosing pancreatic neuroendocrine tumors in patients with multiple endocrine neoplasia type 1 in daily practice - van Beek, Dirk-Jan; Pieterman, Carolina R. C.; Wessels, Frank J.; van de Ven, Annenienke C.; de Herder, Wouter W.; Dekkers, Olaf M.; Zandee, Wouter T.; Drent, Madeleine L.; Bisschop, Peter H.; Havekes, Bas; Borel Rinkes, Inne H. M.; Vriens, Menno R.; et al. (Frontiers in Endocrinology, 2022)
Background: In multiple endocrine neoplasia type 1 (MEN1), pancreatic neuroendocrine tumors (PanNETs) have a high prevalence and represent the main cause of death. This study aimed to assess the diagnostic accuracy of the currently used conventional pancreatic imaging techniques and the added value of fine needle aspirations (FNA). Methods: Patients with at least one imaging study were included from the population-based MEN1 database from the DutchMEN Study Group from 1990–2017. Magnetic resonance imaging (MRI), computed tomography (CT), endoscopic ultrasonography (EUS), FNA, and surgical resection specimens were obtained. The first MRI/CT/EUS was considered as the index test. For a comparison of the diagnostic accuracy of MRI versus CT, patients with their index test between 2010 and 2017 were included. The reference standard consisted of surgical histopathology or radiological follow-up. Results: 413 patients (92.8% of database) underwent 3477 imaging studies. The number of imaging studies per patient increased, and a preference for MRI was observed in the last decade. Overall diagnostic accuracy was good with a positive (PPV) and negative predictive value (NPV) of 88.9% (95% confidence interval 76.0-95.6) and 92.8% (89.4-95.1) for PanNET in the pancreatic head and 92.0% (85.3-96.0) and 85.3% (80.5-89.1) in the body/tail. For MRI, PPV and NPV for pancreatic head tumors were 100% (76.1-100) and 87.1% (76.3-93.6) and for CT 60.0% (22.9-88.4) and 70.4% (51.3-84.3), respectively. For body/tail tumors, PPV and NPV were 91.3% (72.0-98.8) and 87.0% (75.3-93.9) for MRI and 100% (74.9-100) and 77.8% (54.3-91.5) for CT, respectively. Pathology confirmed a PanNET in 106/110 (96.4%) resection specimens. FNA was performed of 34 lesions in 33 patients and was considered PanNET in 24 (all confirmed PanNET by histology (10) or follow-up(14)), normal/cyst/unrepresentative in 6 (all confirmed PanNET by follow-up), and adenocarcinoma in 4 (2 confirmed, 2 PanNET). Three patients, all older than 60 years, had a final diagnosis of pancreatic adenocarcinoma. Conclusion: As the accuracy for diagnosing MEN1-related PanNET of MRI was higher than CT, MRI should be the preferred (non-invasive) imaging modality for PanNET screening/surveillance. The high diagnostic accuracy of pancreatic imaging and the sporadic occurrence of pancreatic adenocarcinoma question the need for routine (EUS-guided) FNA.